Investigating novel drug delivery systems to enhance tissue regeneration in the central nervous system - Lin, Vincent Po Hen (Nanyang Technological University, 2023)
Targeted drug delivery within the central nervous system (CNS) has gained increasing interests in treating neurological diseases, such as neurodegenerative and demyelinating diseases. However, the presence of multiple cell types in the CNS tissues may lead to nonspecific uptake and reduced efficiency in drug delivery. Therefore, an effective approach to target specific cell type in the disease treatment is necessary. In this work, we employed neural cell-derived membrane coating technique on DNA nanogels to improve target specificity. The efficacy of neural cell membrane-coated DNA nanogels (NCM-nanogels) were demonstrated by using four types of cell membranes derived from the CNS, namely, astrocytes, microglia, cortical neurons, and oligodendrocyte progenitor cells (OPCs). A successful coating of neural cell membrane over DNA nanogels was confirmed by dynamic light scattering and zeta potential. Subsequently, the cellular uptake results suggested an overall improvement in cellular uptake of NCM-nanogels over uncoated DNA nanogels (p < 0.005). Additionally, we observed a selective uptake of OPC membrane-coated DNA nanogels (NCM-O mem) by oligodendrocytes. Next, our biomimicking fiber platform was further examined in hope to discover new fiber material that closely mimic the mechanical properties of native neurons, hence allowing more accurate examination of therapeutic outcomes upon drug/gene delivery. Two scaffold materials, namely, polylactic acid-polycaprolactone copolymer (PLA-PCL), and dextran methacrylate (DexMA) were extensively examined. Lastly, an extensive review on injectable hydrogels was carried out to expand our therapeutic strategies in CNS diseases treatment. In this review, the development of injectable hydrogels in stroke and spinal cord injury treatment, focusing on the cellular response and tissue integration, was discussed.